The Future of arXiv. - Robert Michaelson (Issues in Science and Technology Librarianship)
The author discusses the use of arXiv, a repository for high energy physics, cosmology and other areas of physics and mathematics developed by Paul Ginsparg at Los Alamos in 1991. The author comments on a "Chronicle of Higher Education" article about the arXiv being managed by the Cornell University Library and the library's proposed business model which intends to solicit :000 U.S. dollars for the top 100 users of the repository. The author believes that such model is only a transitional model and institutions cannot operate without arXiv.